Teaching Practicum Assessment Procedures Adopted by Primary Teachers’ Colleges during COVID-19 pandemic era in Zimbabwe (Teacher Education through Flexible Learning in Africa (TETFLE), 2022)
The advent of COVID-19 caused massive disruptions to Teaching Practicum (TP) continuity and scheduled assessment activities. This study investigated the assessment tools and procedures adopted by Primary Teachers' colleges in Masvingo province during the COVID-19 pandemic in Zimbabwe. The transformative learning theory underpinned this study. A quantitative research design was used and data was gathered using online questionnaires with both closed and open-ended items. The items solicited information on how colleges transformed assessment tools and procedures during the pandemic for continuity of learning by teacher trainees. Non-probability purposive sampling was used to select respondents. There were 14 respondents, amongst them 13 primary teacher training lecturers and one TP coordinator. Findings indicated that TP assessment strategies did not change from physical lesson observations instead, TP assessments stopped at the peak of the pandemic since schools that host teacher trainees also closed. The completion of the course for teacher trainees was extended.  Where lecturers got access to schools, they resorted to the observation of TP files and supporting documents. It can be concluded that assessment of teaching practicum online remains a challenge and there is a need to change assessment strategies post-COVID-19 pandemic.
Keywords: Assessment, assessors, college lecturers, COVID-19, online teaching, mentors, micro-teaching, teaching practicum, teacher trainees, ZINTEC.